NGURI-URI KEBUDAYAAN JAWA PADA PAKET PERNIKAHAN ADAT JAWA - Suharti, Suharti; Wibawa, Sutrisna; Widyastuti, Sri Harti (Universitas Negeri Yogyakarta, 2010)
The purposes of this program are (1) to motivate student becoming entrepeneurs at the Javanesse wedding traditional ceremony package, (2) to increase the students' entrepeneurship knowledge at the Javanesse wedding traditional ceremony, (3) to create connection between higher education, especially Javanesse Study Program of the Yogyakarta State Universty, and business partners of the Javanesse wedding traditional ceremony package, and (4) to increase the students' and the lectures' capabilities, skills, and practical experiences at conducting of the Javanesse wedding traditional ceremony package. This program has carried out at three stages, those are (1) an upgrading of the development of Javanesse wedding tradisional ceremony package, including MC materials, Javanesse speakers, the Javanesse cultural knowlege, the experiences of conducting wedding package, discussion and practice of determining of the package and suplying clothing, and the knowladge of the entrepreneurship and business operational, (2) conducting of the training at Griya Rias Wijayaningtyas, and (3) work shop of structuring the wedding business plan and simulation of wedding ceremony pakcage. The result of this program are (1) all of the participants have motivation to wrestle with the entrepreneurs of the Javanesse wedding package ompletely or partial, and as an individually or agroup, (2) all of the participants have busness operational plans at the Javanesse wedding package, (3) there is a conection between higher education, especially Javanesse Study Program of Yogyakarta State University, and business partners of the Javanesse wedding traditional ceremony package, and (4) the participants of the students and the lectures have improved their skills, especially in practical skill of the Javanesse wedding ceremony